The Problematics of Turning on The Main Light Lettings For Two-Wheeled Motor Vehicle Under The Laws Number 22 Year 2009 on Traffic And Road Transport - Juliani Prihartini; Alvi Syahrin; Mahmud Mulyadi; Marlina (Mahadi: Indonesia Journal of Law, 2023)
For two-wheeled vehicles, it is expressly required by Law Number 22 of 2009 Concerning Road Traffic and Transportation to switch on the primary lights during the day. A requirement for vehicle eligibility on the road is the regulation of this obligation. The provisions in the UULLAJ do not yet control the ATPM's accountability for vehicle requirements that ensure the headlights stay on and the availability of an automatic device as a warning when the headlights are damaged. This has ramifications for traffic-related duties performed by the National Police in the area of law enforcement. Only drivers who fail to fulfil their requirements to ensure the specifications of their primary lights throughout the day without touching the ATPM are the targets of law enforcement. Because there was no legal framework for the Police to take action against the ATPM, this law enforcement was not carried out. In reality, considerations of legal certainty, justice, and advantages must be given while establishing a legal norm. Data were collected using interviews as main sources and library research as secondary sources. This study employs a qualitative research methodology and is a descriptive analysis.